Contraception at extremes of ages, adolescents and special situations - Nautiyal, Ruchira; Goyal, Priyanka (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Contraception is designed to prevent pregnancy. Selection of contraceptive depends on many factors including a woman’s overall health, age, frequency of sexual activity, number of sexual partners, desire to have children in future, and family history of certain diseases. Hence, planning of pregnancy is of utmost importance to the woman who has in addition a high risk factor. Pregnancy may worsen the preexisting disease or medicines taken for it and vice versa. Therefore, preplanned pregnancy is required with adequate control of high risk factor to ensure optimal pregnancy outcome.